Governing Ideas : Strategies for Innovation in France and Germany. - Ziegler, Nicholas (Cornell studies in political economy., 2019)
Despite increasingly open markets and a pervasive move toward international production methods, national governments continue to pursue remarkably distinctive policies for promoting innovation in industry. J. Nicholas Ziegler analyzes this apparent paradox by comparing government efforts to promote technological advance in Germany and France. His findings reveal a great deal about the roots and limits of public strategies for economic growth. Through close comparison of three technologies- digital telephone exchanges, computer-controlled machine tools, and semiconductors-Ziegler shows how each country displays predictable strengths and weaknesses in promoting innovation. These distinctive capacities depend more upon the links among different skill- and knowledge-bearing elites than on the structure of the state or the industrial sector in question. As business outcomes hinge less on economies of scale and more on knowledge-based competition, the politics of contending interest groups steadily gives way to a competition for status and jurisdiction among more specialized professional groups. As a result, Germany's strengths stem directly from what Ziegler calls an ethos of competence whereas France's strengths stem from an order of state-created elites. More generally, Ziegler contends, neo-institutional approaches to public policy need to pay far more attention to the professional identities of different occupational groups.